Nanotechnology-driven synergy in cardio-oncology: enhancing tumor suppression and reducing cardiotoxicity - Ma, Luyao; Zhang, Bowen; Liu, Xiaomei; Gao, Shengwei; Kong, Shengjie; Li, Yanfen; Wang, Ruihua; Li, Meifeng; Mao, Xinyu; Li, Yuhong; Luo, Yang; Li, Liang; et al. (Frontiers in Pharmacology, 2025)
The integration of nanotechnology into oncology has profoundly reshaped cancer treatment, enabling drug delivery systems with remarkable precision, enhancing antitumor efficacy, and simultaneously addressing major challenges such as cardiotoxicity, one of the most prevalent and serious adverse effects of conventional chemotherapy. This review systematically examines the dual role of nanotechnology, highlighting its capacity to enhance the therapeutic effectiveness of anticancer treatments while concurrently mitigating cardiotoxic side effects. The discussion centers on a broad spectrum of nanocarrier platforms, such as liposome-based, polymeric nanocarriers, and inorganic nanocarriers organized according to their structural features and therapeutic benefits, thereby enabling a systematic comparison with conventional drug delivery strategies. By improving drug bioavailability, enabling controlled release, and achieving precise tumor-specific targeting, these nanocarrier systems enhance antitumor efficacy while concurrently reducing collateral damage to healthy tissues. Moreover, recent preclinical and clinical studies were summarized to demonstrate substantial advances in this interdisciplinary field, while also identifying persistent challenges that remain to be addressed. Finally, the review explores future directions, with particular emphasis on the integration of artificial intelligence to optimize nanocarrier design and the promise of personalized nanomedicine in transforming cancer care. Overall, this work provides a critical foundation for advancing next-generation, patient-tailored cancer therapies.